The Role of Subsidies in Agricultural Development programmes in India - Sree R, Shilpa; S Katti, Medhavini (International Journal of Psychosocial Rehabilitation, 2020)
Every year’s government of India spends lot of money in various agriculture subsidies schemes for growth of agriculture sector. The Government of India uses a different of policy instruments in attempting to achieve these Agriculture goals, including, Domestic subsidies to inputs, outputs, explicit and implicit, transportation, machinery equipment’s, storage, electricity, irrigation, fertilizer, and consumption to reduce producer costs and consumer prices. Input subsidies are the most expensive aspect of India’s food and agriculture policy regime, requiring a steadily larger budget share. The current economic research also highlights the important role of agricultural subsidies in India. In order to examine the linkage between agriculture subsidies and agricultural development programmers or scheme in India and Karnataka. Used statistical tools like table chart etc. This study is based on secondary data collected from NABARD, Budget estimation India, ministry of Agriculture and finance, economic survey of Karnataka etc. Suggested some government policies & programmers.